2012
DOI: 10.1371/journal.pone.0037553
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing-Based Comparative Genome Analysis of Vibrio vulnificus Environmental Isolates

Abstract: Between 1996 and 2006, the US Centers for Disease Control reported that the only category of food-borne infections increasing in frequency were those caused by members of the genus Vibrio. The Gram-negative bacterium Vibrio vulnificus is a ubiquitous inhabitant of estuarine waters, and is the number one cause of seafood-related deaths in the US. Many V. vulnificus isolates have been studied, and it has been shown that two genetically distinct subtypes, distinguished by 16S rDNA and other gene polymorphisms, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 74 publications
7
76
0
Order By: Relevance
“…The first identified 80 cluster-II-specific genes including a set of genes involved in Flp pilus-coding region, GGDEF proteins and genomic island XII. The other (Morrison et al, 2012) identified 278 genes associated with clinical strains including genes involved in sialic acid metabolism, mannitol fermentation and part of a type IV secretory pathway virB. Some of the genes identified in these studies were also found to be differentially expressed in the present study (Flp pilus-coding region, GGDEF proteins, genomic island XII and sialic acid metabolism).…”
Section: Clusters Of Orthologous Groups (Cog) Functional Categories Osupporting
confidence: 58%
See 2 more Smart Citations
“…The first identified 80 cluster-II-specific genes including a set of genes involved in Flp pilus-coding region, GGDEF proteins and genomic island XII. The other (Morrison et al, 2012) identified 278 genes associated with clinical strains including genes involved in sialic acid metabolism, mannitol fermentation and part of a type IV secretory pathway virB. Some of the genes identified in these studies were also found to be differentially expressed in the present study (Flp pilus-coding region, GGDEF proteins, genomic island XII and sialic acid metabolism).…”
Section: Clusters Of Orthologous Groups (Cog) Functional Categories Osupporting
confidence: 58%
“…The set of genes included a cluster involved in sialic acid catabolism and TRAP-transport system (CMCP6 genome VV2_ 0726, VV2_0729, VV2_0731, VV2_0732, VV2_0734 and VV2_0735). This set of genes has been identified in V. vulnificus genotypes associated with human infection (Morrison et al, 2012) and as cluster-II-specific genes . Four genes encoded peptide ABC transporter substrate-binding protein, arylsulfatase and arylsulfatase regulator (YJ016 genome VVA1630, VVA1632, VVA1633 and VVA1634).…”
Section: Clusters Of Orthologous Groups (Cog) Functional Categories Omentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to conventional phenotypic analyses, this PCR method is highly accurate and requires only 3 h from colony selection to species confirmation and genotype determination, which is much faster than other typing methods (34). Subsequent studies using extensive phenotypic analysis (35), multilocus sequence typing (34,36), pulsed field genomic analysis (34,37), and ultimately, whole genome sequencing (38), confirmed the existence of the two biotype 1 genotypes, and the highly significant correlation of the C-genotype with human disease-causing ability. That two distinct genotypes are present in this species was confirmed by the genomic studies of Gulig et al (39) and when we recently sequenced three E-genotype strains and compared them to three previously published C-genotype strains (38).…”
Section: Biotypes and Genotypesmentioning
confidence: 99%
“…Genotyping based on molecular techniques, such as Pulsed-field gel electrophoresis, ribotyping, RAPD-PCR, extragenomic palindromic DNA PCR (Arias et al 1998;Chatzidaki-Livanis et al 2006); multilocus sequence typing (Bier et al 2013;Bisharat et al 2005;Cohen et al 2007;Reynaud et al 2013) and comparative genome analysis (Morrison et al 2012) have shown that V. vulnificus populations could be divided into two genotypes, the C-or the E-type. The C-type has been correlated to clinical origin responsible for human infections, while the E-type to those isolated from environmental origin and considered non-pathogenic.…”
Section: Introductionmentioning
confidence: 99%